STUDI ORGANOLOGI SULING MANDALUNG DALAM SENI TEMBANG SUNDA CIANJURAN - Nanang Jaenudin; Nita Juwita; Ade Triana Nurjaya (LP2M ISBI Bandung, 2026)
Tembang Sunda Cianjuran, created by Dalem Pancaniti in the nineteenth century, has undergone continuous development, particularly in its accompanying instruments, most notably the suling (bamboo flute). Initially, only the six-hole flute and the four-hole flute were used. However, the emergence of song repertoires in the laras mandalung tuning system led to the development of a new flute variant known as the suling mandalung. This study aims to present an organological analysis of the mandalung suling within the context of Tembang Sunda Cianjuran. A qualitative research method was employed, with data collected through literature review, field observation, and interviews. The findings indicate that the suling mandalung emerged as an adaptive response to the mandalung repertoire, which could not be fully accommodated by the six-hole and four-hole flutes Physically, the suling mandalung resembles the six-hole flute but features a shorter body and smaller hole diameter to accommodate the higher acoustic frequencies of the laras mandalung tuning system. Its tuning system also refers to the sorog tuning of the six-hole flute.